Protists [and] fungi [computer file] - Discovery Channel School; ENTREX SOFTWARE; Clock Tower Images, Inc. ([U.S.A.] Discovery Communications, Inc., 2004)
Explores the world of protists and fungi using video segments with animations, documentary footage, interactive experiments/simulations, and interactive multimedia tools with reference tools.
Version 2.0
Minimum system requirements for Windows: Pentium II Processor-based PC or compatible computer (or better), Windows 98/ME/2000/XP, at least 128 MB RAM. Color monitor (high color-10 bit), Quick Time? 6.0 or later (6.0 included on CD), 8x CD-ROM (or faster)
Minimum system requirements for Macintosh: 400 MHz PowerPC or faster Macintosh computer, Mac OS 8.6 or later; Mac OS X v10.1.5; v10.2.3 or later, at least 128 MB RAM, color monitor (thousand colors), Quick Time? 6.0 or later (6.0 included on CD) 8x CD-ROM (or faster)
This CD-ROM discusses topics on plasmodium, the symbiotic relationship of ants and fungi, Pfiesteria piscicida, and ecophysiology of fungi.
Keywords: Plasmodium; Insect -- fungus relationship; Pfiesteria piscicida; Fungi -- Ecophysiology